Réponses

2014-10-07T16:36:58+02:00
A=(4x+4)²-(-x-3)(5x-4)
=16x²+32x+16+5x²-4x+15x-12
=21x²+43x+'4
B=(2x+4)(2x+5)+(9x+6)²
=4x²+10x+8x+20+81x²+108x+36
=85x²+126x+56
C=(5x-4)(5x+4)-(6x-3)²
=25x²-16-36x²+36x-9
=-11x²-36x-25
D=(3x-7)²-(10x-8)²
=9x²-42x+49-100x²+160x-72
=-91x²-118x-23


2014-10-07T16:48:47+02:00
A= 16x²+16+32x - (-5x² +4x -15x +12)
 = 16x² + 16 + 32x + 5x² - 4x +15x -12
 = 21x² +43x + 4
B= 4x²  + 10x + 8 x + 20 + 81 x² + 36 - 108x
 = 85x² -90x + 56
C = 25x² + 20x - 20x - 16 - ( 36x² + 9 - 36x )
   = 25 x² - 16 - 36x² - 9 +36x
   = -11 x² + 36x -25
D=9x² + 49 - 42x - ( 100x² + 64 - 160x)
 = 9x² + 49 - 42x - 100 x² - 64 + 160x
= -91 x² + 118x - 15

G = 4(49x² + 25 + 70x) - 2(4x² +1 - 4x)
= 196 x² + 100 + 280x - 8x² - 2 +8x
= 188x² +288x + 98

Le F) n'est pas visible entièrement ^^
voilà merci